2006 IEEE Information Theory Workshop 2006
DOI: 10.1109/itw.2006.322848
|View full text |Cite
|
Sign up to set email alerts
|

On the Synchronization of Physical-Layer Network Coding

Abstract: When data are transmitted in a wireless network, they reach the target receiver as well as other receivers in the neighborhood. Rather than a blessing, this attribute is treated as an interference-inducing nuisance in most wireless networks today (e.g., IEEE 802.11). Physical-layer network coding (PNC), however, has been proposed to take advantage of this attribute. Unlike "conventional" network coding which performs coding arithmetic on digital bit streams after they are decoded, PNC makes use of the additive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
168
0
2

Year Published

2010
2010
2018
2018

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(171 citation statements)
references
References 4 publications
1
168
0
2
Order By: Relevance
“…In the simulation, 2 Z lattice code of 2 points per-dimension is employed in the two source nodes, which is equivalent to 4-QAM constellation. At the relay node, lattice decoding is used to decode the integer linear combination of the codewords sent from the two users.…”
Section: ) Simulation Verificationmentioning
confidence: 99%
See 1 more Smart Citation
“…In the simulation, 2 Z lattice code of 2 points per-dimension is employed in the two source nodes, which is equivalent to 4-QAM constellation. At the relay node, lattice decoding is used to decode the integer linear combination of the codewords sent from the two users.…”
Section: ) Simulation Verificationmentioning
confidence: 99%
“…The principle of network coding is that intermediate nodes forward functions of received packets rather than individual packets to increase the throughput. In 2006, three research groups [2]- [4] independently proposed the idea of PNC for wireless network. It is shown that, with a relay decoding and forwarding the modulo-two sum (XOR) of the transmitted packets, the throughput of a two-way relay channel can be significantly improved.…”
Section: Introductionmentioning
confidence: 99%
“…Using a suitable mapping scheme, they show that for certain modulation schemes, there exists a mapping scheme such that the relationship between the two transmitted binary bits and the decoded binary bit follows the XOR principle. We here revisit the PNC operation [1] and its mapping scheme to achieve the XOR principle. Consider two senders, N 1 and N 3 , and a common receiver N 2 .…”
Section: Decoding a Collision A Physical-layer Network Codingmentioning
confidence: 99%
“…For BPSK, we have a j = 2s j − 1 [1]. At N 2 , a scheme (see Table I) that maps a strong energy signal to binary 0 (i.e.…”
Section: Decoding a Collision A Physical-layer Network Codingmentioning
confidence: 99%
“…Nevertheless, the amount of improvement is different due to applying different NC schemes, which encourages researchers to work on this field. In this regard, Physical-layer Network Coding (PNC or PLNC) [19] and Analog Network Coding (ANC) [20] were devised to attain more capacity by exploiting simultaneous transmission.…”
Section: Introductionmentioning
confidence: 99%